How to Be a Man?: Masculinity Construction in a Short Story Mina’s Eid Cake’s Secret (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims to describe the masculinity construction between the characters in the short story Secret of Mina’s Lebaran Cake. The research data was gathered by a review of the literature. The descriptive analysis of the data obtained is the method adopted in this study. Data was gathered through a review of the literature. Following data collection, descriptive analysis was carried out as follows: (1) attentively reading literary works; (2) marking the part of the short tale that incorporates a feminist narrative; (3) data were analyzed using a masculinity approach; and (4) data were interpreted. The analysis and interpretation results are then provided. The findings of this study reveal that patriarchy and the development of masculinity produce tension in the gender roles accepted by the characters in the short narrative. Patriarchy not only confines and creates women, but it also molds boys to conform to the "might’’ that men create and spread.